Gender as Potential Moderator of Associations Among Trauma Exposure, Posttraumatic Stress Disorder Symptoms, and Alcohol Use Disorder Symptoms in Young Adults. Issue 4 (10th July 2019) - Bremer‐Landau, Jodi D.; Caskie, Grace I. L.
Abstract: Traumatic events (TEs), posttraumatic stress disorder (PTSD) symptoms, and alcohol use disorder (AUD) symptoms can significantly impair functioning, yet little is known about whether associations among these variables differ between men and women within young adult samples. The current study conducted a path analysis of archival, longitudinal data from the Drug Use Trajectories: Ethnic/Racial Comparisons 1998–2002 (DUT) study (Turner, 2011) to examine gender differences as a possible moderator of the relations between TEs, PTSD symptoms, and AUD symptoms among 1, 076 young adults (aged 18–23 years) residing in South Florida. The sample included 580 male (53.9%) and 496 female (46.1%) participants, whose ethnicity was self‐reported as African American ( n = 280, 26.0%), non‐Hispanic White ( n = 268, 24.9%), other Hispanic ( n = 267, 24.8%), and Cuban ( n = 261, 24.3%). Significant positive associations were found between TEs and PTSD symptoms, βs = .08–.30; PTSD and AUD symptoms, βs = .09 – .10; PTSD symptoms over time, β = .52; and AUD symptoms over time, β = .46. In addition, for male but not female participants, a higher frequency of PTSD symptoms at Wave I was related to more AUD symptoms at Wave II, β = .09. Findings build upon existing research to further elucidate the role of gender as a potential moderator of the associations among TEs, PTSD symptoms, and AUD symptoms for young adults and provide important implications for future research and clinical practice, including informing mental health prevention and treatment efforts. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) El género como posible moderador de las relaciones entre Trauma, síntomas del Trastorno de Estrés Postraumático, y síntomas del trastorno por consumo de alcohol en adultos jóvenes . GÉNERO, EXPOSICIÓN AL TRAUMA. TEPT Y CONSUMO DE ALCOHOL. Los eventos traumáticos (ETs), los síntomas del trastorno de estrés postraumático (TEPT) y los síntomas del trastorno por consumo de alcohol (TCA) pueden afectar significativamente el funcionamiento, pero se sabe poco acerca de si las asociaciones entre estas variables difieren entre hombres y mujeres en una muestra de adultos jóvenes. El presente estudio llevó a cabo un análisis de ruta de los datos longitudinales archivados de las trayectorias de consumo de drogas: Estudio de Comparaciones Étnica/Racial 1998–2002 (DUT en sus siglas en inglés) (Turner, 2011) para examinar las diferencias de género como posible moderador de las relaciones entre los ETs, los síntomas de TEPT y los síntomas de TCA entre 1, 076 adultos jóvenes (de 18 a 23 años) que residen en el sur de Florida. La muestra incluyó 580 participantes, hombres (53.9%) y 496 mujeres (46.1%), cuya etnia fue autorreportada como afroamericanos ( n = 280, 26.0%), blancos no hispanos ( n = 268, 24.9%), otros hispanos ( n = 267, 24.8%), y cubanos ( n = 261, 24.3%). Se encontraron asociaciones positivas significativas entre ETs y los síntomas de TEPT, βs = .08‐.30; los síntomas de TEPT y los síntomas de TCA, βs = .09‐.10; los síntomas de TEPT con el tiempo, β = .52; y los síntomas de TCA con el tiempo, β = .46. Además, para los participantes masculinos pero no femeninos, se encontró una frecuencia más alta de síntomas de TEPT en la medición I la cual se relacionó con más síntomas de TCA en la medición II, β = .09. Los hallazgos se basan en investigaciones existentes para dilucidar aún más el papel del género como posible moderador de las asociaciones entre los ETs, los síntomas del TEPT y los síntomas de la TCA en adultos jóvenes, y proporcionan importantes implicancias para la investigación futura y la práctica clínica, incluida la información sobre la prevención y el tratamiento de la salud mental. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Gender as Potential Moderator of Relations Between Trauma, Posttraumatic Stress Disorder Symptoms, and Alcohol Use Disorder Symptoms in Young Adults Traditional Chinese 標題: 初成年人士中, 性別作為創傷 、創傷後壓力症症狀、酒精使用失常症狀的關連間潛在的調節變量 撮要: 創傷事件(TEs)、創傷後壓力症(PTSD)症狀、酒精使用失常(AUD)症狀皆可對功能運作構成顯著傷害。可是, 我們並不清楚這些變量之間的關連是否會在初成年的樣本中因性別而生異。本研究對「藥物使用軌跡:種族比較1998–2002 (DUT)研究(Turner, 2011)」中的縱貫數據進行路徑分析, 檢視性別差異是否為TEs、PTSD 症狀及AUD症狀的關連間潛在的調節變量。樣本為居於南佛羅里達州1, 076名初成年人士(年齡為 18–23 歲)。樣本中有580名男性(53.9%) 、496 名女性 (46.1%)。透過自評報告所得的種族比例為:非裔美國人(n = 280, 26.0%)、非西班牙裔白人(n = 268, 24.9%)、其他西班牙裔人(n = 267, 24.8%)、古巴人(n = 261, 24.3%)。TEs 與 PTSD 症狀之間(βs = .08–.30)以及PTSD與 AUD 症狀之間(βs = .09– .10), 都有顯著的正向關連;隨時間發展, PTSD 症狀之間 (β = .52)及AUD症狀之間(β = .46)亦有顯著的正向關連。此外, 男性樣本中, PTSD 症狀頻率在第一波較高, 跟第二波有較多AUD症狀有關(β = .09)。是次發現進一步延伸過往的研究, 闡明在初成年人士中, 性別是TEs、PTSD 症狀及AUD症狀的關連間潛在的調節變量, 並為未來研究和臨床工作提供重要資料, 包括有關心理健康的保障和治療方法的建議。 Simplified Chinese 标题: 初成年人士中, 性别作为创伤 、创伤后压力症症状、酒精使用失常症状的关连间潜在的调节变量 撮要: 创伤事件(TEs)、创伤后压力症(PTSD)症状、酒精使用失常(AUD)症状皆可对功能运作构成显著伤害。可是, 我们并不清楚这些变量之间的关连是否会在初成年的样本中因性别而生异。本研究对「药物使用轨迹:种族比较1998–2002 (DUT)研究(Turner, 2011)」中的纵贯数据进行路径分析, 检视性别差异是否为TEs、PTSD 症状及AUD症状的关连间潜在的调节变量。样本为居于南佛罗里达州1, 076名初成年人士(年龄为 18–23 岁)。样本中有580名男性(53.9%) 、496 名女性 (46.1%)。透过自评报告所得的种族比例为:非裔美国人(n = 280, 26.0%)、非西班牙裔白人(n = 268, 24.9%)、其他西班牙裔人(n = 267, 24.8%)、古巴人(n = 261, 24.3%)。TEs 与 PTSD 症状之间(βs = .08–.30)以及PTSD与 AUD 症状之间(βs = .09– .10), 都有显著的正向关连;随时间发展, PTSD 症状之间 (β = .52)及AUD症状之间(β = .46)亦有显著的正向关连。此外, 男性样本中, PTSD 症状频率在第一波较高, 跟第二波有较多AUD症状有关(β = .09)。是次发现进一步延伸过往的研究, 阐明在初成年人士中, 性别是TEs、PTSD 症状及AUD症状的关连间潜在的调节变量, 并为未来研究和临床工作提供重要资料, 包括有关心理健康的保障和治疗方法的建议。